Development of a gearing mechanism for a robotic finger / Hamzah Ab Wahab - Ab Wahab, Hamzah (2011)
In this report, the study of a suitable gearing system for robotic finger is the main focused. Many types of gears have been considered such as planetary gearing system, harmonic gearing system, spur gear and bevel gear, in order to select the most suitable gear in accordance to the application of the gearing system for the robotic finger. The objective of this project is to design and model the gearing mechanism for the robotic finger. The project phases begin with designing and modeling of the gearing system. The clash and interference analysis by using CATIA is done to the gearing system. The gearing model will then be fabricated by using rapid prototyping process and tested to determine the working performance of the robotic finger. The purpose of the testing is to analyze the speed and force produced from the movement of the robotic finger. As a result, if the movement of the robotic finger is found to be acceptable and as desired, then the gearing system is said to be suitable for the robotic finger application.